Pemanfaatan Pseudomonas Fluorescens untuk Pertumbuhan Sengon di Lahan Bekas Tambang Kapur - Eugenia Marcella Hotmauli Manik; M. Akbari Danasla (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Abandoned mining sites often experience a decline in soil fertility, which impacts soil quality and agricultural sustainability. This study aims to explore the potential of Pseudomonas fluorescens in rehabilitating limestone mining lands and enhancing the growth of Sengon (Falcataria moluccana) trees grown in polybag media. Sengon was selected as a pioneer species due to its resilience in degraded soils and its ability to improve soil structure. This study used an experimental design involving eight different treatments, which included the application of manure and varying concentrations of Pseudomonas fluorescens. Evaluations were conducted on the 25th and 50th days by measuring plant growth parameters such as plant height, root length, and key soil chemical properties, including pH, organic carbon, total nitrogen, total phosphorus, total potassium, and cation exchange capacity (CEC). The results showed that the application of 15 mL of Pseudomonas fluorescens on day 50 resulted in optimal plant growth, as indicated by an increase in plant height, root length, and soil quality improvement. The application of Pseudomonas fluorescens also enhanced soil pH, organic carbon, total nitrogen, and cation exchange capacity, all of which contributed to the improvement of soil fertility in the limestone mining land. This study provides evidence that Pseudomonas fluorescens can play a role in the rehabilitation of abandoned mining lands and improve the growth of Sengon trees, contributing to the recovery of degraded ecosystems.